Involvement or inequality? Perceptions of client involvement in digital services among social and health care professionals and clients - Weiste, Elina; Rydman, Vilja; Kurki, Anna-Leena (Finnish Journal of eHealth and eWelfare, 2022)
Promoting client involvement is one of the central aims in the digitalization of social and health care services. This study examines the perceptions of social and health care clients, employees and managers about client involvement in digital services. The aim is to increase the understanding of the relationship between client involvement and digitalization, as well as the similarities and differences between the perceptions of clients and professionals. The study is based on thematic interviews of 86 people in five social and health care organizations in the public sector in Finland. The method used is qualitative, theory-based content analysis. Perceptions of client involvement in digital services was classified into five categories: the client as a recipient of services, the client as a feedback provider, the client as an interaction partner, the client as an independent actor outside service encounter and the client as a developer. The analysis highlighted the tensions within the categories: each category was associated with the possibilities for ideal client involvement and, on the other hand, the realities of the digitalization, as well as the new challenges posed by it. Clients highlighted concerns related to digital services: fears about the adequacy of skills and support, as well as reduced interaction. Managers emphasized the potentials of digitalization, especially in communication, giving feedback and service development. Employees highlighted both challenges and possibilities, with particular emphasis on access to services, feedback and remote appointments. In digital services, the client’s role as an independent actor and information seeker is emphasized. Simultaneously, the client’s choices and decisions are easily hidden from the professionals and the dialogue remains limited. This raises a wide range of concerns among both clients and professionals. Understanding the perceptions of the various stakeholders is therefore important when designing and developing digital services for social and health services.